One in three: challenging heteronormative assumptions in family planning health centers - Everett, Bethany G. (Contraception, 2018)
OBJECTIVES: To estimate the prevalence of sexual-minority women among clients in family planning centers and explore differences in LARC uptake by both sexual identity (i.e., exclusively heterosexual, mostly heterosexual, bisexual, lesbian) and sexual behavior in the past 12 months (i.e., only male partners, both male and female partners, only female partners, no partners) among those enrolled in the survey arm of the HER Salt Lake Contraceptive Initiative. METHODS: This survey categorized participants into groups based on reports of sexual identity and sexual behavior. We report contraceptive uptake by these factors, and we used logistic and multinomial logistic models to assess differences in contraceptive method selection by sexual identity and behavior. RESULTS: Among 3901 survey respondents, 32% (n=1230) identified with a sexual-minority identity and 6% had had a female partner in the past 12 months. By identity, bisexual and mostly heterosexual women selected an IUD or implant more frequently than exclusively heterosexual women and demonstrated a preference for the copper T380 IUD. Exclusively heterosexual and lesbian women did not differ in their contraceptive method selection, however, by behavior, women with only female partners selected IUDs or implants less frequently than those with only male partners. CONCLUSION: One in three women attending family planning centers for contraception identified as a sexual minority. Sexual-minority women selected IUDs or implants more frequently than exclusively heterosexual women. IMPLICATIONS: Providers should avoid care assumptions based upon sexual identity. Sexual-minority women should be offered all methods of contraception and be provided with inclusive contraceptive counseling conversations.